Safe water and sanitation in remote Indigenous communities in Australia: conditions towards sustainable outcomes. Issue 2 (3rd July 2022) - Hall, Nina Lansbury; Abeysuriya, Kumudini (Kumi); Jackson, Melissa; Agnew, Charles; Beal, Cara D.; Barnes, Samuel K.; Soeters, Simone; Mukheibir, Pierre; Brown, Suzanne; Moggridge, Bradley
ABSTRACT: Safe drinking water and effective sanitation is a basic human right. The health of Aboriginal and Torres Strait Islander Peoples living on traditional Country in remote Australia can be supported or undermined by these essential services. Despite global and Australian commitments to the Sustainable Development Goals, water and sanitation service levels have regularly been identified as unreliable, unsafe, and of a lower standard than non-Indigenous and non-remote settlements. This research sought to identify the optimal conditions to enable consistent delivery of safe water and sanitation in remote Indigenous communities of Australia. Using a combination of literature reviews, interviews with key stakeholder groups and applied research findings, key conditions for improved water and sanitation outcomes were identified. These included technology for water and sanitation that is fit for purpose, people and place; capacity-building, training and ongoing support for local Indigenous service operators; and that all personnel involved in delivery require a level of cultural competency to the local and Indigenous context. These findings are intended to contribute to informing more sustainable water and sanitation outcomes in Indigenous communities.